ANALISIS PERBEDAAN KUALITAS LABA DAN NILAI PERUSAHAAN SEBELUM DAN SESUDAH ADANYA KOMITE PADA BANK-BANK GO PUBLIC DI INDONESIA - Fendi Permana Widjaja; Rovila El Maghviroh (Universitas Hayam Wuruk Perbanas, 2011)
Quality of earnings and firm value are the factors found to be interesting for the researchrecently. This study aims to determine differences in earnings quality and firm value beforeand after the committee audit. It is initially motivated by the different research resultsconducted y previous researchers. Yet, up to now, there isn’t any research that examinessuch factors in the banking industries by comparing the time series. In this research,earnings quality is measured using changes in total accruals and the ratio of quality ofincome, while the company’s value is measured using price to book value and Tobin’s Q.The samples are publicly traded banks in Indonesia, with the total of 12 companies. Thesample is taken by means of purposive sampling method. The period observed in this study isthree years before and after the audit. The result of the calculation of earnings quality(changes TA and the ratio of quality of income) and corporate value (price to book value andTobin’s Q) showed little effect of audit committee on earnings quality and company valuewhich is indicated by statistical test that there isn’t difference of quality earnings and valueof companies before and after the committee audit. This shows that within three years of thecommittee audit cannot perform their duties optimally